Antimicrobial Susceptibility Profile at Uganda Martyrs Hospital Lubaga, Kampala Uganda (London Journal of Medical and Health Research, 2025)
The majority of infectious diseases are of bacterial in origin. With the discovery of laboratory methods to grow these microorganisms using an appropriate growth medium known as “culture,” determining the sensitivity and resistance of specific pathogens to a wide range of antimicrobial agents is necessary so clinicians can immediately institute proper treatment regimens. (Bayot& Bragg, 2024) This targeted approach of treatment is considered the gold standard however most clinicians use or opt for empiric antibiotic therapy as an approach to treat the suspected infection. This has resulted into irrational use of antibiotics in clinical practice hence and emerging antimicrobial resistance.Antimicrobial resistance (AMR) has emerged as a major threat to public health globally. (Gajic et al 2022) An estimated 1.14 million deaths were directly caused by antimicrobial resistance (AMR) in 2021 worldwide, and it is projected that over 39 million people will die from AMR-related infections between 2025 and 2050 (GBD 2021).This public health crisis has potential severe implications for resource-limited settings. However, accurate and rapid detection of resistance to antimicrobial drugs, and subsequent appropriate antimicrobial treatment, combined with antimicrobial stewardship, are essential for controlling the emergence and spread of antimicrobial resistance.  (Gajic et al 2022).Therefore, the purpose of this study is to:  develop an antibiogram to   empower doctors to make informed prescribing decisions in the clinic regarding use of antibiotics at Uganda martyrs’ hospital Lubaga and to generate data regarding the concept to bring greater clarity to this issue.
Keywords: Risk factors; Surgery; mortality; Trauma; Chest; Wound.; disease incidence; Coronavirus Disease-19; Acute Invasive Fungal; Rhinosinusitis; Chronic kidney disease; Multiple Myeloma; Differential Diagnosis (Source: MeSH; NLM)